The Effect of Hydrotherapy on Pain Intensity and Functional Ability in Lumbar Disk Herniation (LDH) Patients that Undergo Non-operative Procedure Pre-experimental Study at Medical Rehabilitation Installation of RSUP dr. Mohammad Hoesin Palembang - Rahmadhani, Theresa; Nyimas Fatimah; Eka Febri Zulissetiana (Sriwijaya Journal of Medicine, 2020)
The effect of hydrotherapy on pain intensity and functional ability in lumbar disk herniation (LDH) patients thatundergo non-operative procedure; pre-experimental study at medical rehabilitation installation of RSUPdr. Mohammad Hoesin Palembang. Lumbar disk herniation (LDH) is the most common disease that becaused low backpain and functional disability. Some studies mentioned that hydrotherapy is an effective treatment for low back pain.Therefore, this study was conducted to determine the effect of hydrotherapy on reducing pain intensity and improvingfunctional ability in LDH patients. This study was a pre-experimental study with one group pretest-posttest design. Datawas collected by direct interviews to the patients using visual analogue scale (VAS) to measure pain intensity andModified Oswestry Low Back Pain Disability Questionnaire to assess functional ability before and after underwenthydrotherapy once a week for 4 weeks. The data then undergo Shapiro-Wilk normality test and continue with Paired t-Test or Wilcoxon test. From 30 subjects, it was found that there are effects of hydrotherapy on reducing pain intensity(p<0,001) and improving functional ability (p<0,001) in LDH patients that undergo non-operative procedure at theMedical Rehabilitation Installation of RSUP Dr. Mohammad Hoesin Palembang. There are effects of hydrotherapy onpain intensity and functional ability in LDH patients that undergo non-operative procedure.